A Tale of Two Networks: Contrasting Sport for Development and Peace Actor-Networks. Issue 4 (2nd October 2019) - Richelieu, André; Webb, Andrew
Abstract: This study highlights the convergence, contrasts, and coherence between two sport for development and peace (SDP) actor-networks. Overall, some coherence, but much contrast, between academic and practitioner actor-networks is demonstrated. The lack of theoretical knowledge about how and why practitioners construct actor-networks is also emphasized. Moreover, important academic questions—such as why scholars' understanding of actor-networks are based on a dominant, yet questionable, vision of how sport influences development and peace—are raised. Critical perspectives about the theoretical underpinnings of sport for development and peace and the influence that shifting funding priorities have on sport for development and peace actor-networks are brought to the fore.